Per Capita Income – Based on Sangam Era - D, Ramasamy (International Research Journal of Tamil, 2022)
Porunar, Pulavar, Panar, Koudhar, Patini, Varaviyar are known as Iravalars (beggers). They are called as Iravalars because they earn their living by singing. In their songs, they praise the rich people and as gift, they get gifts, money and so on. The rich people also go in search of Iravalars, because they love to hear their songs in praise of them. Sangha literary texts speaks abundantly and extensively about the people living as Iravalars and how they earn their income by singing praise of others.